2018
DOI: 10.3390/jof4030079
|View full text |Cite
|
Sign up to set email alerts
|

Present and Future Therapy of Cryptococcus Infections

Abstract: Cryptococcal infections burden the immunocompromised population with unacceptably high morbidity and mortality. This population includes HIV-infected individuals and those undergoing organ transplants, as well as seemingly immunocompetent patients (non-HIV, non-transplant). These groups are difficult to manage with the current therapeutic options and strategies, particularly in resource-limited settings. New trials aimed at providing the best treatment strategies for resource-limited countries that will reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 56 publications
(72 reference statements)
0
48
0
1
Order By: Relevance
“…There is a constant need for new, cheaper, less toxic, and widely available drugs for cryptococcosis treatment ( Coelho and Casadevall, 2016 ; Mourad and Perfect, 2018a , b ). In this way, South America’s biodiversity can be a rich source of new molecules ( Valli et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a constant need for new, cheaper, less toxic, and widely available drugs for cryptococcosis treatment ( Coelho and Casadevall, 2016 ; Mourad and Perfect, 2018a , b ). In this way, South America’s biodiversity can be a rich source of new molecules ( Valli et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current treatment of cryptococcal meningoencephalitis consists of an induction, consolidation, and maintenance regimen ( Mourad and Perfect, 2018a ). The Infectious Disease Society of America (IDSA) recommends a 2-week treatment with amphotericin B (AMB) and flucytosine (5-FC) followed by treatment with fluconazole with time frame and dose depending on the patient’s response ( Perfect et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic Cryptococcus species complexes, Cryptococcus neoformans and Cryptococcus gattii , are the etiological agents of cryptococcosis, an invasive fungal disease with a high mortality rate and high public health costs worldwide ( Mourad, 2018 ). These fungi generate different clinical and epidemiological consequences, which depend mainly on the immunity of the host and the pathogenicity of the agent ( Rajasingham et al, 2017 ; George et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cryptococcal meningitis (CM) caused by Cryptococcus (C.) neoformans infection is a serious infectious disease of the central nervous system (CNS) [1,2]. CM is associated with high rates of mortality and morbidity, and as with other CNS fungal infections, Therefore, CM has a severe economic impact on healthcare systems [2,3]. A paediatric study of CM from China reported that the majority of patients were apparently normal, and only 23.5% had identifiable underlying conditions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the clinical characteristics and therapeutic outcomes of CM [1,2,[7][8][9], however the clinical characteristics and therapeutic outcomes of young adults with CM have not been examined solely in the literature. In this study, we examined the clinical and laboratory features and therapeutic outcomes of young adults with CM in order to delineate the clinical characteristics of this specific group of CM patients.…”
Section: Introductionmentioning
confidence: 99%